Innovations in materials manufacturing, fabrication, and environmental safety - Schwartz, Mel M. (Boca Raton, FL : CRC Press, 2011)
'With contributions from a panel of experts from industry, government, and academia, this volume is a practical guide to the latest innovations in materials processing and fabrication. It examines current and developing processes in the aerospace, industrial, commercial, military, and electronic industries. Coverage for each process spans the testing background, why and where it is being used, applications, potential to replace existing processes, and environmental and safety concerns. The various processes and fabrication methods include friction stir welding, infusion mold technologies, heat treatment processing, plasma brazing, diffusion and adhesive bonding, and laser processes'--
Includes bibliographical references and index.
Keywords: Manufacturing processes -- Technological innovations